2018
DOI: 10.3168/jds.2017-14251
|View full text |Cite
|
Sign up to set email alerts
|

Hot topic: Pregnancy-induced expression of interferon-stimulated genes in the cervical and vaginal mucosal membranes

Abstract: In ruminants, IFN-tau (IFNT) is a pregnancy recognition signal secreted by the embryonic trophectoderm before implantation, and it induces the expression of IFN-stimulated genes (ISG) in the uterine endometrium and blood leukocytes. The expression of ISG in blood leukocytes could indicate the presence of a viable conceptus before return of the next estrus; however, expression levels have high variation for confirming pregnancy. We hypothesized that the secreted IFNT in the uterus would affect ISG expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Maternal recognition of pregnancy in cattle occurs during the period of embryo elongation when IFNT is secreted by trophectoderm cells of the developing conceptus (Bazer et al, 1997;Gray et al, 2002) to prevent the release of PGF 2α by the endometrium, thus maintaining the CL function and P4 production (Bazer et al, 2015). In addition to its role in the process of maternal recognition of pregnancy, IFNT is also able to induce the expression of several ISG by the endometrium (Mirando et al, 1991) and reaches the peripheral circulation through the uterine vein (Oliveira et al, 2008;Bott et al, 2010), leading to the expression of ISG in extra-uterine sites such as the CL (Oliveira et al, 2008), liver (Ruhmann et al, 2017) vaginal and cervical mucosa (Kunii et al, 2018) and peripheral blood leukocytes (Yankey et al, 2001;Han et al, 2006;Kizaki et al, 2013).…”
Section: Interferon-tau Stimulated Genesmentioning
confidence: 99%
“…Maternal recognition of pregnancy in cattle occurs during the period of embryo elongation when IFNT is secreted by trophectoderm cells of the developing conceptus (Bazer et al, 1997;Gray et al, 2002) to prevent the release of PGF 2α by the endometrium, thus maintaining the CL function and P4 production (Bazer et al, 2015). In addition to its role in the process of maternal recognition of pregnancy, IFNT is also able to induce the expression of several ISG by the endometrium (Mirando et al, 1991) and reaches the peripheral circulation through the uterine vein (Oliveira et al, 2008;Bott et al, 2010), leading to the expression of ISG in extra-uterine sites such as the CL (Oliveira et al, 2008), liver (Ruhmann et al, 2017) vaginal and cervical mucosa (Kunii et al, 2018) and peripheral blood leukocytes (Yankey et al, 2001;Han et al, 2006;Kizaki et al, 2013).…”
Section: Interferon-tau Stimulated Genesmentioning
confidence: 99%
“…Mx1 gene is expressed in maternal liver during late periimplantation period, which is induced by embryonic signal IFNT in the bovine (Meyerholz et al, 2016). Mx1 mRNA is upregulated in the cervix, vagina and blood neutrophils during early pregnancy in cows (Kunii et al, 2018;Sheikh et al, 2018). Mx1 interacts with tubulin beta in the ovine glandular epithelial cells during interphase and mitosis, and is implicated in intracellular trafficking and secretion in ovine uterus during early pregnancy (Racicot et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated ISG mRNA abundance us-ing peripheral blood mononuclear cells (PBMC). Recently, other studies have used total immune cells from whole blood (Yoshino et al, 2018) or milk (Schanzenbach et al, 2017) or cervical and vaginal mucosa cells (Kunii et al, 2018) for accessing gene expression and predicting pregnancy status. In addition, novel potential pregnancy markers were recently reported by our group in beef heifers (Rocha et al, 2020) and need to be tested for early pregnancy diagnosis in dairy cattle.…”
Section: Short Communication Physiologymentioning
confidence: 99%
“…Therefore, although the use of whole blood for extraction of mRNA in circulating immune cells is simple and faster for applied use, this method results in reduced accuracy for pregnancy prediction and is still not feasible to replace the use of PBMC or granulocytes. Kunii et al (2018) reported that ISG15 expression in cervical and vaginal mucosal membranes of pregnant cows is significantly greater than that in nonpregnant cows. These authors also observed a greater fold change of ISG15 expression in CC of pregnant animals, indicating that the closer location of the cervix in relation to the embryo may result in greater IFN-τ stimuli for ISG transcription.…”
Section: Short Communication Physiologymentioning
confidence: 99%
See 1 more Smart Citation